Role of interferon regulatory factor 5 (IRF5) in the regulation of t helper cytokines - Amar Singh, Ashwinder Kaur (2021)
Interferon regulatory factor 5 (IRF5) has a diverse role in the induction of pro-inflammatory cytokines and chemokines downstream to various signalling pathways contributing to the pathogenesis of various autoimmune and inflammatory diseases. Using Irf5 knockout mice under different experimental settings, studies have reported that IRF5 plays a crucial role in T helper (Th) polarization. Previous studies have shown that IRF5 has a potential role in regulating Th2 cytokine production, particularly Interleukin-13 (IL-13). Sequence analysis human Il13 promoter showed the presence of the IFN sensitive response element (ISRE) motif, the region that IRFs can recognize through their helix turn helix nucleotide domain. As a transcription factor, IRF5 has been shown to recognize and bound to this region to regulate the expression of its targeted genes. Based on these findings, we were intrigued to examine the transcriptional role of IRF5 in regulating the expression of human IL-13 and assess the modulation of IRF5 in regulating the expression of Th1 and Th2 associated cytokines.